1634 : the Ram rebellion - Flint, Eric (Ring of fire (Riverdale, N.Y.), 2007)
As the Thirty Years War continues to ravage seventeenth-century Europe, the West Virginians from twentieth-century America enter into an alliance with Gustavus Adolphus, King of Sweden, to promote a revolution among the peasants who seek freedom from the tyrannical nobility of the period.